IMPLEMENTASI METODE NAÏVE BAYES PADA APLIKASI SISTEM PAKAR BERBASIS WEB UNTUK MENDIAGNOSA KERUSAKAN PADA HARDWARE KOMPUTER - Eric Agung Lestari Jiwono; Syaiful Rahman; Hasniati (STMIK KHARISMA Makassar, 2017)
Improper use on computer can cause a lot of damages especially on the hardware. Even though sometimes the damages are severe, there’s also simple damages. The goals of this study are to design and implement webbased expert system using Naïve Bayes method that can process the rules of computer condition to conclude final answer to the problem and then measure the performance. It begins with making data-flow diagram and entity-relationship diagram. Then, we implements that with PHP as programming language and MySQL as database. Based on research result, the author has managed to build expert system application to diagnose computer hardware problems with 100% accuracy based on 18 test samples with the average time of execution is 0.158845 seconds. With that, visitors can easily understand the nature of their computer problems and how to solve it.